1988
DOI: 10.1007/bf00578406
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and pharmacodynamic properties of a new controlled-release formulation of metoprolol: A comparison with conventional tablets

Abstract: The pharmacokinetic and pharmacodynamic properties of a new multiple-unit, controlled-release (CR) formulation of metoprolol (metoprolol succinate, 95 mg once daily), which has almost constant (zero-order) release properties over most of a 24-h dose interval, have been compared with those of conventional metoprolol tablets (metoprolol tartrate, 100 mg once daily and 50 mg twice daily), in 12 healthy male volunteers. The steady-state plasma concentrations of metoprolol after five days of treatment varied less t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
0
5

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(95 citation statements)
references
References 6 publications
5
85
0
5
Order By: Relevance
“…38 The MERIT-HF trial enrolled 3991 subjects with ischemic and nonischemic dilated cardiomyopathies who had class II through IV heart failure 38 ; the metoprolol preparation used was a continuous release (CR), single-daily-dose formulation of coated metoprolol succinate pellets. 79 Importantly, the average dose of metoprolol achieved in MERIT-HF was larger than in MDC, 159 versus 108 mg. Most subjects (97%) enrolled in MERIT-HF were categorized as class II or III heart failure, and on the basis of the annualized mortality of 11% in the placebo group and the baseline left ventricular ejection fraction of 28%, this landmark clinical trial enrolled subjects with mild to moderate heart failure and moderate to severe systolic dysfunction.…”
Section: ␤-Blockers In Chf 561mentioning
confidence: 99%
See 2 more Smart Citations
“…38 The MERIT-HF trial enrolled 3991 subjects with ischemic and nonischemic dilated cardiomyopathies who had class II through IV heart failure 38 ; the metoprolol preparation used was a continuous release (CR), single-daily-dose formulation of coated metoprolol succinate pellets. 79 Importantly, the average dose of metoprolol achieved in MERIT-HF was larger than in MDC, 159 versus 108 mg. Most subjects (97%) enrolled in MERIT-HF were categorized as class II or III heart failure, and on the basis of the annualized mortality of 11% in the placebo group and the baseline left ventricular ejection fraction of 28%, this landmark clinical trial enrolled subjects with mild to moderate heart failure and moderate to severe systolic dysfunction.…”
Section: ␤-Blockers In Chf 561mentioning
confidence: 99%
“…79 The bioavailability of the CR preparation is Ϸ70% of the conventional formulation. 77 However, compared with 50 mg BID of the conventional formulation, 100 mg of the CR preparation produces similar trough levels and degrees of reduction in exercise heart rate, indicating bioequivalence of the 2 preparations.…”
Section: ␤-Blockers In Chf 561mentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma levels during carvedilol and metoprolol treatment and elimination half-life of carvedilol were in agreement with previously published reports. 14,17 At these concentrations, metoprolol blocks Ϸ50% of ␤ 1 -ARs but Ͻ5% of ␤ 2 -ARs, whereas carvedilol blocks Ͼ90% of both ␤ 1 -and ␤ 2 -ARs. 7 However, because metoprolol displays higher inverse agonist activity than carvedilol, 6,7 these concentrations reduced contractile force in human myocardium by similar extents (43% and 32%, respectively 7 ).…”
Section: In Vivo Experimentsmentioning
confidence: 99%
“…Good tolerability would be expected because metoprolol is a 1 selective -blocker and the peak plasma concentrations in individuals taking metoprolol CR/ZOK are low (14)(15). Further clinical trials have demonstrated a low incidence of adverse effects (16).…”
Section: Metoprolol Cr/zokmentioning
confidence: 99%